Bingo capitalism the law and political economy of everyday gambling - Bedford, Kate 1975- (Oxford University Press, 2019)
Casinos are often used by political economists, and popular commentators, to think critically about capitalism. Bingo - an equal chance numbers game played in many parts of the world - is overlooked in these conversations about gambling and political economy. Bingo Capitalism challenges that omission by asking what bingo in England and Wales can teach us about capitalism and the regulation of everyday gambling economies. The book draws on official records of parliamentary debate, case law, regulations and in-depth interviews with both bingo players and workers to offer the first socio-legal account of this globally significant and immensely popular pastime. It explores the legal and political history of bingo and how gender shapes, and is shaped by, diverse state rules on gambling. It also sheds light on the regulation of workers, players, products, places, and technologies. In so doing it adds a vital new dimension to accounts of UK gambling law and regulation.through Bingo Capitalism, Bedford makes a key theoretical contribution to our understanding of the relationship between gambling and political economy, showing the role of the state in supporting and then eclipsing environments where gambling played a key role as mutual aid. In centering the regulatory entanglement between vernacular play forms, self-organized membership activity, and corporate leisure experiences, she offers a fresh vision of gambling law from the everyday perspective of bingo.